Sustainable agriculture and food security - Shiva,Vandana .(ed.) (New Delhi, 2002)
Sustainable agriculture is based on the sustainable use of natural resources land, water and agricultural biodiversity, including that of plants and animals. The sustainable use of these, in turn, requires that their ownership and control lie with decentralised agricultural communities to generate livelihoods, provide food and conserve natural resources. These three dimensions of ecological security, livelihood security and food security are the essential elements of an agriculture policy which is sustainable and equitable. This book shows how the processes of globalization threaten to undermine all three dimensions, and calls for immediate action.
Keywords: Food industry and trade